1985
DOI: 10.1016/0736-5748(85)90052-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biochemical maturation of rat astroglial cells grown in a chemically defined medium: Influence of an astroglial growth factor

Abstract: Astroglial cells from cerebral hemispheres of newborn rats were cultured for 5 days in Waymouth's MD 705/1 medium containing 10% fetal calf serum. Thereafter, cells were grown in a chemically defined medium consisting of basal Waymouth's medium supplemented with insulin (5 μg/ml) and fatty acid free bovine serum albumin (0.5 mg/ml). The cells underwent morphological and biochemical development over a period of 28 days. The changes in the amount of glial fibrillary acidic protein indicated a development of glio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…AGF and FGF, proteins with established mitogenic and differentiation-promoting effects for glial cells and derivatives of mesoderm origin (3)(4)(5)(6)10), were found also to be trophic for neurons cultured from embryonic peripheral and central nervous systems. Neurotrophic actions comprised (i) promotion of survival, (ii) neuritic growth, and (iii) induction of transmitter-synthesizing enzyme ChoAcTase activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AGF and FGF, proteins with established mitogenic and differentiation-promoting effects for glial cells and derivatives of mesoderm origin (3)(4)(5)(6)10), were found also to be trophic for neurons cultured from embryonic peripheral and central nervous systems. Neurotrophic actions comprised (i) promotion of survival, (ii) neuritic growth, and (iii) induction of transmitter-synthesizing enzyme ChoAcTase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, nerve growth factor has been shown to act as a mitogen on rat pheochromocytoma (1) and adrenal medullary chromaffin cells (2). On the other hand, FGF and astroglial growth factors (AGF-1 and -2) that are closely related or even identical to acidic and basic FGF (aFGF, bFGF) (3) induce proliferation and differentiation of neuroectodermal astroglial cells (4), oligodendrocytes (5,6), and neuron-like PC-12 pheochromocytoma cells (7).…”
mentioning
confidence: 99%
“…In addition, bFGF also influences proliferation and differentiation of glial cells [2,3]. Recently, in vivo and in vitro studies have shown that bFGF exerts neurotrophic actions in the peripheral (PNS) and central nervous system (CNS) [4-g].…”
Section: Introductionmentioning
confidence: 99%
“…After 2-3 weeks nearly all cells in these cultures contain glial fibrillary acidic protein (GFAP) [2], Therefore, these cells have been regarded as a uniform population of astroblasts with similar properties. How ever, when the astrocytes were cultured in a chemically defined medium [3,4], they showed a more heterogenous aspect: some cells exhibited a flat and polygonal shape, others were more elongated and extend several protoplasmic processes. Moreover, it has been found that not all cultured astro cytes present glutamine synthetase (GS) [3][4][5], that a small subgroup of astrocytes accumulates glycogen [6] and that only a subpopulation of astrocytes synthesize the proteinase inhibitor a2-macroglobulin [7],…”
Section: Introductionmentioning
confidence: 99%